Early Marriage in the Flexing Era: A Review of Law and Ethics on Social - Hasan, Amir; Hasibuan, Rahyana (El-Sirry: Jurnal Hukum Islam dan Sosial, 2024)
Early marriage in Indonesia has become a complex and pressing issue, particularly in the context of the digital era known as "flexing." This study employs a qualitative approach with a descriptive method to deeply explore the phenomenon of early marriage within the legal and ethical contexts of social media, as well as to understand the perspectives of both teenagers and parents regarding the decision to marry at a young age. The findings indicate that early marriage is influenced by various social, cultural, and economic factors, including strong societal norms, pressure from social environments, and the impact of social media that promotes young marriage as a status symbol. Despite the existence of legal regulations prohibiting early marriage, such as Law No. 16 of 2019 concerning Marriage, its implementation remains ineffective on the ground. The impacts of early marriage are felt not only by individuals but also by families and society as a whole, creating cycles of poverty and long-term health issues. This research highlights the importance of government and community roles in addressing this issue through educational programs and awareness campaigns. Proposed policy recommendations include developing comprehensive sex education programs and promoting children's rights, as well as providing economic support for low-income families